DEVELOPMENT OF INFRASTRUCTURAL LINKS OF INNOVATIVE SYSTEM KAZAKHSTAN IN THE CONDITIONS OF FORMATION OF SCIENTIFIC ECONOMY - B. B. Korgan , (Academic Journal of Physical and Chemical Sciences, 2019)
Formation of the organization of innovation in the Republic of Kazakhstan is one of the leading places in the development of the country itself. In Kazakhstan, the last few years, interest in innovation has grown very significantly - even at the level of the government, measures to stimulate innovation have been taken. Innovation activity in Kazakhstan has not yet received the theoretical and practical level that would help overcome the technological gap, change the nature and production volumes in all sectors of the economy. This article identifies the functional role of NIS RK, as well as each of its subsystems in the formation of an innovation-type economy. The data on the development of the scientific and technical system, innovation infrastructure and innovation activities of the country are presented.